2005
DOI: 10.1074/jbc.m408253200
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Conductance Is Required for the Protein Kinase A and Rac1-dependent Phosphorylation of Moesin at Thr-558 by KCl in PC12 Cells

Abstract: Moesin is a member of the ERM family, a family of cross-linkers between the plasma membrane and the actin cytoskeleton, which are known to be activated by phosphorylation. Previously, we reported the RhoA and Rho kinase-dependent phosphorylation of moesin at Thr-558 in hippocampal neuronal cells by glutamate. Here we studied the induction of moesin phosphorylation by KCl (60 mM) in PC12 cells. Moesin phosphorylation at Thr-558 was increased after 2 min of KCl treatment, peaked at 5 min, and returned to the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(64 reference statements)
0
5
0
2
Order By: Relevance
“…Quercetin of 10 µM stimulated the NGF-induced neurite outgrowth in culture medium containing 61. 6 [31][32][33][34][35][36][37][38][39][40], gene expression of epithelial sodium channel via a PTK-dependent pathway [4], and cell migration via remodeling of cytoskeleton [41][42][43]. In addition, Menegazzi and colleagues [5,44] have reported that physiological functions of neutrophil (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin of 10 µM stimulated the NGF-induced neurite outgrowth in culture medium containing 61. 6 [31][32][33][34][35][36][37][38][39][40], gene expression of epithelial sodium channel via a PTK-dependent pathway [4], and cell migration via remodeling of cytoskeleton [41][42][43]. In addition, Menegazzi and colleagues [5,44] have reported that physiological functions of neutrophil (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of P. gingivalis to establish an oral infection is facilitated by prior antibioticmediated suppression of the murine oral flora and may exploit inter-bacterial interactions with early colonizers as has been proposed for the human oral cavity (Daep, et al, 2006;Jeon, et al, 2005). Although vendors may claim that mice are pathogen-free, this does not necessarily mean that they are free of potential periodontal pathogens.…”
Section: Oral Gavage Model Of Experimental Mouse Periodontitismentioning
confidence: 99%
“…In melanocytes, SCF‐induced lamellipodium formation is Rac1‐dependent (Ballestrem et al., 2000), suggesting that Rac may be a downstream mediator of PI3K stimulated by SCF in melanocytes. Recently, we reported that the KCl‐induced phosphorylation of moesin was Rac‐dependent in PC 12 cells (Jeon et al., 2005) and that nerve growth factor‐induced phosphorylation of moesin was mediated through PI3K/Rac/Akt activation in PC12 cells (S. Jeon, B. S. Koo, Y. S. Kim, C. D. Bae and J. Park, unpublished data), which suggest the possibility that the ERM (ezrin/radixin/moesin) proteins family could be a downstream target of Rac in SCF‐treated melanocytes.…”
Section: Introductionmentioning
confidence: 99%